Art About Art - Lipman, Jean; Marshall, Richard; Steinberg, Leo; North Carolina Museum of Art, Raleigh; The Frederick S. Wight Art Gallery, University of California, Los Angeles; Portland Art Museum, Portland (New York : Whitney Museum of American Art, 1978)
de Andrea, John ; Andrejevic, Milet ; Arakawa, Shusaku ; Arneson, Robert ; Baldessari, John ; Boucher, François ; Brancusi, Constantin ; Braque, Georges ; Calder, Alexander ; Capa, Robert ; Caroompas, Carole ; Case, Reginald ; Cézanne, Paul ; Chamberlain, John ; Puvis de Chavannes, Pierre ; Clarke, John Clem ; Colescott, Robert ; Copley, John Singleton ; Cornell, Joseph ; Cottingham, Robert ; Courbet, Gustave ; Cranach, Lucas ; Dali, Salvador ; David, Jacques Louis ; Deem, George ; Degas, Edgar ; Delacroix, Eugène ; Demuth, Charles ; Denes, Agnes ; Diebenkorn, Richard ; Dine, Jim ; Dossi, Dosso ; Downey, Juan ; Dubuffet, Jean ; Duchamp, Marcel ; Edelson, Mary Beth ; Estes, Richard ; van Eyck, Jan ; Flack, Audrey ; Freed, Hermine ; Gauguin, Paul ; van Gogh, Vincent ; Goya, Francisco ; Gray, Bunn ; Graziani, Sante ; Grieger, Scott ; Grooms, Red ; Haberle, John ; Halsman, Philippe ; Hefferton, Phillip ; Hicks, Edward ; Hokusai ; Hurson, Michael ; Indiana, Robert ; Ingres, Jean-Auguste-Dominique ; Jackson, Richard ; Johns, Jasper ; Johnson, Ray ; Kienholz, Edward ; Kline, Franz ; de Kooning, Willem ; Kottler, Howard ; Kuniyoshi, Utagawa ; Leslie, Alfred ; Leutze, Emanuel ; Levi, Josef ; Lichtenstein, Roy ; Loran, Erle ; Magritte, René ; Manet, Edouard ; Marden, Brice ; Marisol ; Matisse, Henri ; McGarrell, James ; Michals, Duane ; Michelangelo ; Mondriaan, Piet ; Monet, Claude ; Morley, Malcolm ; Moroni, Giovanni Battista ; Morris, Robert ; Morse, Samuel ; Nevelson, Louise ; Newman, Barnett ; Noguchi, Isamu ; O'Keeffe, Georgia ; Oldenburg, Claes ; Peto, John Frederick ; Pettibone, Richard ; Phillips, Ammi ; Picasso, Pablo ; Pisanello, Vittorio ; Poussin, Nicolas ; Pratt, Matthew ; Ramos, Mel ; Rauschenberg, Robert ; Rembrandt ; Renoir, Pierre Auguste ; etc.
Art About Art, Whitney Museum of American Art, New York, July 19 - September 24, 1978 ; North Carolina Museum of Art, Raleigh, North Carolina, October 15 - November 26, 1978 ; The Frederick S. Wight Art Gallery, University of California, Los Angeles, December 17, 1978 - February 11, 1979 ; Portland Art Museum, Portland, Oregon, March 6 - April 15, 1979
Engels
boek
Keywords: Amerika